THE XENOLITHS OF GRANULITE-ECLOGITE GROUP FROM ALKALINE ULTRAMAFIC DYKES AND PIPES OF THE KANDALAKSHA GRABEN - Kortshkova M.Yu. (My University, 1998)
According to estimated temperatures and pressures (700-860°C, 13-20 kb) the xenoliths of the grabuliteeclogite group from alkaline ultramafic dykes and pipes of the Kandalaksha graben come from the low crust. The mineral chemistry of the xenoliths depends on both the bulk rock composition and the PT-equilibrium conditions. There are systematic changes in the mineral compositions when garnet-free websterites and granulites turn to Gr-websterites and further to eclogites. The chemistry and geochemistry of the rocks evidence that the granulite-eclogite xenoliths group is heterogeneous. Ancient crust material exhausted with partial melting, ancient subducted oceanic crust, and basalt underplating could be the sources of the xenoliths.